A Simple Entropic‐Driving Separation Procedure of Low‐Size Silver Clusters, Through Interaction with DNA. Issue 8 (5th August 2021) - Buceta, David; Dominguez, Blanca; Vieitez, Sara; Arias, Iria R.; Ageitos, J. Manuel; Blanco, M. Carmen; Barone, Giampaolo; Domínguez, Fernando; López‐Quintela, M. Arturo
Abstract: Synthesis and purification of metal clusters without strong binding agents by wet chemical methods are very attractive for their potential applications in many research areas. However, especially challenging is the separation of uncharged clusters with only a few number of atoms, which renders the usual techniques very difficult to apply. Herein, we report the first efficient separation of Ag2 and Ag3 clusters using the different entropic driving forces when such clusters interact with DNA, into which Ag3 selectively intercalates. After sequential dialysis of the samples and denaturalizing the DNA‐Ag3 complex, pure Ag2 can be found in the dialysate after extensive dialysis. Free Ag3 is recovered after DNA denaturation. Abstract : Uncharged Ag2 and Ag3 clusters synthesized by a wet chemical procedure based on kinetics control, without using strong binding ligands, are separated by a simple procedure due to their very different chemical properties, namely, the different interaction with DNA. Using the specific intercalation ability of Ag3 with DNA, and the corresponding large entropy created in the surrounding water, we report a sequential dialysis/washing procedure allowing the complete separation of both type of clusters.